Benefit of Anakinra in Treating Pediatric Secondary Hemophagocytic Lymphohistiocytosis. Issue 2 (26th December 2019) - Eloseily, Esraa M.; Weiser, Peter; Crayne, Courtney B.; Haines, Hilary; Mannion, Melissa L.; Stoll, Matthew L.; Beukelman, Timothy; Atkinson, T. Prescott; Cron, Randy Q.
Abstract : Objective: To assess the benefit of the recombinant human interleukin‐1 receptor antagonist anakinra in treating pediatric patients with secondary hemophagocytic lymphohistiocytosis (HLH)/macrophage activation syndrome (MAS) associated with rheumatic and nonrheumatic conditions. Methods: A retrospective chart review of all anakinra‐treated patients with secondary HLH/MAS was performed at Children's of Alabama from January 2008 through December 2016. Demographic, clinical, laboratory, and genetic characteristics, outcomes data, and information on concurrent treatments were collected from the records and analyzed using appropriate univariate statistical approaches to assess changes following treatment and associations between patient variables and outcomes. Results: Forty‐four patients with secondary HLH/MAS being treated with anakinra were identified in the electronic medical records. The median duration of hospitalization was 15 days. The mean pretreatment serum ferritin level was 33, 316 ng/ml and dropped to 14, 435 ng/ml (57% decrease) within 15 days of the start of anakinra treatment. The overall mortality rate in the cohort was 27%. Earlier initiation of anakinra (within 5 days of hospitalization) was associated with reduced mortality ( P = 0.046), whereas thrombocytopenia (platelet count <100, 000/μl) and STXBP2 mutations were both associated with increased mortality ( P = 0.008 and P = 0.012, respectively). In considering patients according to their underlying diagnosis, those with systemic juvenile idiopathic arthritis (JIA) had the lowest mortality rate, with no deaths among the 13 systemic JIA patients included in the study ( P = 0.006). In contrast, those with an underlying hematologic malignancy had the highest mortality rate, at 100% (n = 3). Conclusion: These findings suggest that anakinra appears to be effective in treating pediatric patients with non–malignancy‐associated secondary HLH/MAS, especially when it is given early in the disease course and when administered to patients who have an underlying rheumatic disease.